Analysis Geostatistics of Earthquake-proof Parameters and of Construction in a Road Sector of High Vertical Growing - Zabala Rosales, José Andrés (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The purpose of this work is to relate through geostatistics functions (Kriging and Cokriging), the elastic parameters of the ground and the Standard Penetration Testing (SPT). And of this way it will allow the first densification, with the knowledge of the second, in the area located between the Panamericana highway and the Americas avenue of Merida city. The geostatistics analysis allows the estimation of a variable point in an unknown sample space. Therefore, in the case of a defined sector in this study, which has a higher dense vertical growing area in Merida city and where the ground testing has been done for specific purpose, such as the construction of multifamiliar houses, it is isolated in its context geographic, with the intention of establishing the grade of correlation space between them as well as correlation function that allows it to identify elastic-earthquake-proof parameters of the ground with relation to the information obtained from the SPT. That is to say the sample space information, where the common points involved with geophysic information and the SPT, you can determine the possible lateral variations of the ground at a lower cost, from a view point of the area covered with the quantity of the penetration done.